Pasteurella Endocarditis: A Case Report and Statistical Analysis of the Literature - Randall S. Porter; Christine M. Hay (Case Reports in Infectious Diseases)
Pasteurella is a genus of commensal bacteria of the oral cavity of several domesticated animals and a common cause of cellulitis after animal bites. Pasteurella has also been reported as a rare cause of endocarditis, with only 35 prior cases of definite Pasteurella endocarditis in the literature. Here, we present a case of Pasteurella multocida endocarditis treated successfully with surgery and antibiosis, as well as a review of the literature with statistical analysis of correlations between risk factors and clinical outcomes, as well as between treatment choices and clinical outcomes. Despite the small sample size, our analysis indicates a statistically significant correlation between comorbid liver disease and mortality, as well as a significant negative correlation between surgical treatment and mortality. This analysis implies a need for surgical management of endocarditis due to Pasteurella species and for more aggressive management of Pasteurella endocarditis in the setting of comorbid liver disease.